Prolonged mosquitocidal activity of Siparuna guianensis essential oil encapsulated in chitosan nanoparticles. - Taciano P Ferreira; Khalid Haddi; Roberto F T Corrêa; Viviana L B Zapata; Tathyana B Piau; Luis F N Souza; Swel-Marks G Santos; Eugenio E Oliveira; Luis O V Jumbo; Bergmann M Ribeiro; Cesar K Grisolia; Rodrigo R Fidelis; et al. (Public Library of Science (PLoS), 2019)
Background The use of synthetic insecticides is one of the most common strategies for controlling disease vectors such as mosquitos. However, their overuse can result in serious risks to human health, to the environment, as well as to the selection of insecticidal resistant insect strains. The development of efficient and eco-friendly insect control is urgent, and essential oils have been presented as potential alternatives to synthetic insecticides. Moreover, nanoencapsulation techniques can enhance their efficiency by protecting from degradation and providing a controlled release rate. Results We assessed the potential of chitosan nanoparticles in encapsulating Siparuna guianensis essential oil, and maintaining its efficiency and prolonging its activity for the control of Aedes aegypti larvae. The encapsulation was characterized by scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FTIR), and thermogravimetric analysis (TGA), with an encapsulation efficiency ranging from 84.8% to 88.0%. Toxicity studies have demonstrated efficacy against mosquito larvae over 50% for 19 days with 100% mortality during the first week. This persistent action is presumably due to the enhanced contact and slow and maintained release conferred by chitosan nanoparticles. Furthermore, the exposure of aquatic non-target organisms (e.g. embryos and small adult fishes) revealed adequate selectivity of these nanoparticles. Conclusions The encapsulation of S. guianensis essential oil in chitosan nanoparticles showed promising potential as a larvicide control alternative and should be considered within strategies for fighting Ae. aegypti.